Do Social Role-Based Strategies Matter For Gen-Y Customers? The Case Of Indonesian Islamic Banks - Putri Swastika (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2020)
Since its conception, Islamic banks (IBs) have been perceived to be more society-oriented than its counterpart. IBs are expected to engage with their customers in the higher ethical norm, more philanthropic activities, and also concern with their impact on society. Such conceptions become customers’ bold line in distinguishing IBs and conventional banking. As one of the most important customers, understanding Generation-Y behavior is imperative in achieving and maintaining the sustainability of IBs. It includes whether the on-going conception still matters for this segment. The findings of this research demonstrate that Gen-Y consumer concern on relationship satisfaction than trust and identification factors, where relationship satisfaction is influenced by commercial performance, followed by ethical behavior and relational outcomes. Thus, the results suggest some key strategics for IBs maintaining loyalty of Gen-Y customers.Semenjak kemunculannya, Perbankan Syariah (IB) dianggap lebih berorientasi kepada masyarakat (berperan sosial) ketimbang Perbankan Konvensional. IB diharapkan untuk berperilaku lebih etis, lebih dermawan, dan lebih peduli terhadap dampak kegiatan mereka ke masyarakat. Prinsip ini menjadi pembeda antara kegiatan IB dan Konvensional. Menjadi salah satu nasabah paling penting, memahami perilaku nasabah Gen-Y menjadi keharusan dalam mencapai bisnis yang berkelanjutan. Penelitian ini termasuk menganalisa apakah prinsip peranan sosial ini masih penting bagi segmen Gen-Y. Hasil menunjukan bahwa nasabah Gen-Y lebih peduli kepada kepuasan hubungan ketimbang faktor kepercayaan dan identifikasi. Kepuasan hubungan dipengaruhi oleh kinerja komersial, diikuti oleh perilaku etis dan nilai hubungan. Hasil ini merekomendasikan beberapa strategi kunci bagi IB untuk menjaga loyalitas nasabah Gen-Y.